The effect of resistance training set configuration on strength, power, and hormonal adaptation in female volleyball players - Arazi, H.; Khanmohammadi, A.; Asadi, A.; Haff, G. G. (Applied Physiology, Nutrition, and Metabolism, 2018)
The primary purpose of this investigation was to determine the impact of altering the set structure during an 8-week resistance training program on anthropometric, hormonal, and strength power characteristics. Thirty female volleyball players were recruited for participation and then randomly assigned to 1 of 3 resistance training groups: (i) cluster sets (CRT; n = 10), (ii) traditional sets (TRT; n = 10), or (iii) control (CON; n = 10). All athletes were evaluated for thigh and arm circumference, vertical jump, 20-m sprint, 4 × 9-m shuttle-run, 1-repetition maximum (1RM) back squat, bench press, military press, and deadlift prior to and after an 8-week periodized training intervention. Blood samples were taken before and after the 8-week training period to evaluate resting testosterone, cortisol, and insulin-like growth factor 1 responses to the training period. After 8 weeks of training the CRT group displayed a small but significant improvement in vertical jump (CRT: effect size (ES) = 038, 7.1%) performance when compared with the TRT group (ES = 0.34, 5.6%). Both the CRT and TRT training interventions resulted in very large increases in the 1RM squat (CRT: 8.4% ± 1.2%; TRT: 7.3% ± 0.6%), bench press (CRT: 8.3% ± 2.0%; TRT: 8.7% ± 1.9%), military press (CRT: 5.7% ± 1.2%; TRT: 5.5% ± 1.6%), and deadlift (CRT: 8.2% ± 1.6%; TRT: 8.3% ± 2.2%). There were no significant differences in 20-m sprint or 4 × 9-m shuttle run times between the CRT, TRT, and CON groups. These results suggest that cluster sets allow for greater improvements in vertical jump performance and equal improvements in strength gains to those seen with traditional sets.